ErbB-2, the preferred heterodimerization partner of all ErbB receptors, is a mediator of lateral signaling. - Graus-Porta, D (1997)
We have analyzed ErbB receptor interplay induced by the epidermal growth factor (EGF)-related peptides in cell lines naturally expressing the four ErbB receptors. Down-regulation of cell surface ErbB-1 or ErbB-2 by intracellular expression of specific antibodies has allowed us to delineate the role of these receptors during signaling elicited by: EGF and heparin binding EGF (HB-EGF), ligands of ErbB-1; betacellulin (BTC), a ligand of ErbB-1 and ErbB-4; and neu differentiation factor (NDF), a ligand of ErbB-3 and ErbB-4. Ligand-induced ErbB receptor heterodimerization follows a strict hierarchy and ErbB-2 is the preferred heterodimerization partner of all ErbB proteins. NDF-activated ErbB-3 or ErbB-4 heterodimerize with ErbB-1 only when no ErbB-2 is available. If all ErbB receptors are present, NDF receptors preferentially dimerize with ErbB-2. Furthermore, EGF- and BTC-induced activation of ErbB-3 is impaired in the absence of ErbB-2, suggesting that ErbB-2 has a role in the lateral transmission of signals between other ErbB receptors. Finally, ErbB-1 activated by all EGF-related peptides (EGF, HB-EGF, BTC and NDF) couples to SHC, whereas only ErbB-1 activated by its own ligands associates with and phosphorylates Cbl. These results provide the first biochemical evidence that a given ErbB receptor has distinct signaling properties depending on its dimerization.